G144(P) Case report: patient with kaposiform haemangioendothelioma and kasabach merrit syndrome. (May 2019) - Kothari, T; Mathe, N; Alacorn, A; Thompson, F; Koodiyedath, B
Abstract : A female infant was born with a firm mass on the right lower leg. Her bloods showed platelet and consumption coagulopathy, she required platelet transfusion (lowest platelet count was 19×10 9  and Fibrinogen was 0.8 g/L). Ultrasound scan showed a well-defined slightly heterogeneous soft tissue mass that measured 49 mm ×29 mm × 49 mm in keeping with a diagnosis of Rapidly Involuting Capillary Haemangioma (RICH). However, due to persistent thrombocytopenia needing further transfusions, a biopsy was performed. Histology was consistent with Kaposiform Haemangioendothelioma (KHE). KHE is a rare, locally aggressive vascular tumour that occurs in infancy. KHE may rarely involve other internal organs. The incidence is 0.07 per 1 00 000 per year and both genders are affected equally. Half of the cases present at birth and it is frequently complicated by a consumptive coagulopathy, referred to as Kasabach Merritt Syndrome (KMS) which occurs in 70% of cases. Abnormal endothelium and tumor like vasculature promote platelet adhesion, which leads to thrombocytopenia and ongoing fibrosis causes coagulopathy. Vincristine used as neo adjuvant therapy is the most popular treatment choice. It promotes endothelial apoptosis. Vincristine has a low side effect profile and it has been shown to achieve effective tumour shrinkage with resolution of thrombocytopenia. After eight weeks of treatment with Vincristine, her platelet count improved considerably and the lesion became less prominent.